ChemInform Abstract: Regioselective Thorpe—Ziegler Cyclization of 3‐O‐Alkylated Thiophenes; Access to Aminothieno[3, 2‐b]furans and Aminothieno[3, 4‐b]furans. Issue 1 (3rd January 2013) - Gadais, Charlene; Hesse, Stephanie; Kirsch, Gilbert
Abstract It is demonstrated that base promoted intramolecular condensation occurs preferentially on the adjacent nitrile group rather than at an ester or at a ketone substituent.